2015
DOI: 10.1007/978-3-319-14163-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Lone Pair-π Interactions from Electrostatic Viewpoint

Abstract: Over the last two decades, studies on lone pair-π interaction have attracted lot of attention of experimental as well as theoretical chemists due to its intriguing nature and its suspected presence in biological systems. The present Chapter begins with a brief overview of the earlier theoretical and experimental work done in this area. This is followed by exploration of the nuances of bonding in lone pair-π interaction, employing the tool of molecular electrostatic potential (MESP) since such weak interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…Lone pair-p (lp-p)i nteractions, and their subclass, anion-p interactions, are an important binding mode occurring in biomolecules. [1][2][3][4] They were suggested to stabilizes tructures of nucleic acids [1,5] and proteins, [6,7] andt oi nterferew ith protein-DNA [6] and enzyme-substrate [8] recognition.G enerally,l p-p interactions occurring in biological systems are classifieda s "non-covalent", and our recent energy decompositiona nalysis of water-uracil and water-indole lp-p interactions hasi ndeed revealed that in these cases, the covalent component is weak (< 2.5 kcal mol À1 ). This was shown to be due to the large energy gap between the donor (lp) and acceptor( p*) orbitals, and to their inefficientoverlap.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lone pair-p (lp-p)i nteractions, and their subclass, anion-p interactions, are an important binding mode occurring in biomolecules. [1][2][3][4] They were suggested to stabilizes tructures of nucleic acids [1,5] and proteins, [6,7] andt oi nterferew ith protein-DNA [6] and enzyme-substrate [8] recognition.G enerally,l p-p interactions occurring in biological systems are classifieda s "non-covalent", and our recent energy decompositiona nalysis of water-uracil and water-indole lp-p interactions hasi ndeed revealed that in these cases, the covalent component is weak (< 2.5 kcal mol À1 ). This was shown to be due to the large energy gap between the donor (lp) and acceptor( p*) orbitals, and to their inefficientoverlap.…”
mentioning
confidence: 99%
“…To summarize, theoretical chemists frequently classify lp-p (includinga nion-p)i nteractions as noncovalent, [4] in spite of availablee xperimental evidencef or the existence of anion-p CT complexes. [26][27][28] For instance, flavin-anion interactions occurring in crystal structures of flavoproteinsw ere recently explained on the basis of the positive electrostatic potential of the p-face of flavin.…”
mentioning
confidence: 99%
“…The Br lone pair•••π bonding represents attractive interaction between a lone pair electron of Br and a π -system of the up-tilted bromophenyl ring. [27][28][29] This type of interaction was also reported to stabilize the formation of biological macromolecules, [30,31] and binding of inhibitors in the binding pocket of biochemical receptors. [32] In addition, NCI analysis highlights [1] the attractive interaction regions as marked in green disks in the areas of BCP (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Such interaction with the most nucleophilic site of the solute would also be predicted in other models based on the MESP analysis, such as the EPIC model of Gadre. 43,65,41 However, our methodological approach demonstrates that only the S4 isomer that lies 10 kJ/mol above the global minimum involves such an interaction. The only isomer that was identified on the basis of experimental data is the S1 isomer.…”
Section: Identification Of Complementary Sites Of Interactionsmentioning
confidence: 80%
“…Furthermore, such an approach allows the identification of lone pairs by analogy with Lewis structures of the species. 41,42,43 As we will see in the "Methodological Approach" section, we sought to develop a more general approach, based on the identification of every electrophilic and nucleophilic sites of both partners, in order to identify all possible directions of favorite approaches, in line with the concepts developed by Politzer, Murray, Scheiner, de Proft and collaborators. This approach allows us to propose initial isomeric structures for the complexes.…”
Section: Introductionmentioning
confidence: 99%